Clinical phenotyping of cardiogenic shock at a glance: A rapid, costless, streamlined approach - Miloud Cherbi; Hamid Merdji; Eric Bonnefoy; François Roubille; Clément Delmas; for the FRENSHOCK Investigators (ESC Heart Failure)
Abstract Aims Cardiogenic shock (CS) is a heterogeneous syndrome in which recent guidelines have proposed clinical phenotyping based on the presence of hypoperfusion and/or congestion signs and symptoms. However, the impact of this clinical phenotype on outcomes remains poorly characterized. Methods and results FRENSHOCK is a prospective registry including 772 CS patients from 49 centres. Patients were categorized into multiple phenotypic groups based on three clinically assessed bedside criteria at admission: congestion, hypotension and skin mottling. The primary endpoint was 30‐day all‐cause mortality. Among 475 CS patients included, 69.7% were male, with a median age of 67.0 (59.0–78.0) years. Most patients presented with SCAI stage C (37.1%) or D (51.2%). At admission, 424 patients (89.3%) presented with congestion (50.7% on both sides, 39.2% left‐sided, 10.1% right‐sided), 343 (72.2%) with hypotension and 180 (37.9%) with mottling. At 30 days, 113 patients (23.8%) had died, spanning from 8.8% for patients with isolated hypotension (without congestion/mottling) to 26.5% for patients with hypotension and congestion, and 32.3% for patients with hypotension, congestion and mottling. The corresponding ORs for 30‐day all‐cause mortality remained significant even after adjustment for potential confounders, with 1.19 [(1.02–1.39), P = 0.03] for hypotension and congestion and 1.26 [(1.08–1.48), P < 0.01] for hypotension, congestion and mottling. Conclusions A simple clinical bedside evaluation of the CS phenotype based on hypotension, congestion and mottling allows for quick and costless stratification of 30‐day mortality risk and can be used to guide the level of monitoring intensity and/or patient management.